The Effect of Campus Infrastructure on Student Decision Making in Choosing to Study at HKBP Nommensen Pematang Siantar University T.A 2019/2020 - Elvi Suryani Sitompul; Sotarduga Sihombing; Herlina Hotmadinar Sianipar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of campus infrastructure on student decision making in choosing courses at HKBP Nomensen Pematangsiantar University for the 2019/2020 academic year. This type of research is descriptive quantitative research. The population in the study was 103 students of economic education in the 2019/2020 academic year. The sample used in this study was 103 by taking the entire population of economics education students at HKBP Nommensen Pematang Siantar University T.A 2019/2020 using the sampling technique, namely the Saturated Sample. Based on data analysis using Excel, it was found that the infrastructure variable (X) had no influence on student decision making in choosing courses at HKBP Nomensen Pematangsiantar University for the 2019-2020 Academic Year. Where in testing the hypothesis of the infrastructure variable (X) where the t-count value is 10.06 > the t-table value is 1.660, it can be concluded that infrastructure (X) has a significant influence on decision making (Y). After carrying out inferential statistical analysis, the statistical equation obtained from linear regression is Y = a + bX. The statistical equation obtained in this study is Y = 1.207 + 0.998 X. This can be interpreted that if the decision-making value increases by one unit, the campus infrastructure will increase by 0.998. It can be concluded that H_0 is accepted and H_1 is rejected. In the sense that the infrastructure variable has no effect on student decision making in choosing to study at HKBP Nomensen Pematangsiantar University.